Bracha Lichtenberg Ettinger: matrixial borderline - Buci-Glucksmann, Christine; Lichtenberg, Bracha Ettinger; Jabès, Edmond 1912-1991 (Herblay, France Les cahiers des regards, 1993)
Bracha Lichtenberg-Ettinger is an Israeli-French artist, psychoanalyst and feminist theorist, who was born in Tel Aviv and is currently working in Paris. She received her Ph.D. in Aesthetics of Art from the University of Paris VIII, a D.E.A. in Psychoanalysis from the University of Paris VII, and an M.A. in Clinical Psychology from the Hebrew University of Jerusalem. Her paintings have been exhibited extensively internationally in major museums of contemporary art, and can be found in public collections. She is the author and coauthor of several books and numerous essays.